Enhancement of Creep Lifetime of Aluminum through Severe Plastic Deformation - Petr Král; Jiří Dvořák; Marie Kvapilová; Andrej G. Kadomtsev; Václav Sklenička (Crystals, 2024)
This work investigates the creep behavior of severely deformed commercial aluminum. The commercial aluminum was processed by helical rolling (HR) and equal-channel angular pressing (ECAP) at room temperature. During these processes, the equivalent strain up to about 4 was imposed into the as-received material. The creep testing at 200 °C revealed that HR and ECAP significantly increased the time to fracture compared to the as-received material. The stress dependences showed that the value of stress exponent n decreased with the value of the imposed strain. The stress-change tests showed that as-received and severely deformed states exhibited different recovery rates after unloading. The microstructure analysis showed that creep behavior was influenced by the microstructure formed during severe plastic deformation. The relationships between creep behavior and microstructure in the investigated states are discussed.